1983
DOI: 10.1055/s-2007-1017455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Putative Antidepressant, Rolipram, on the Circadian Running Wheel Activity of a Day-active Chipmunk, Eutamias sibiricus

Abstract: Siberian chipmunks (Eutamias sibiricus) were kept individually in small cages attached to a running wheel. Under continuous illumination of two different light intensities (0.4-0.9 lux and 400-1200 lux) the influence of Rolipram, a putative new antidepressant, on the period length tau was tested. Under both conditions Rolipram caused a lengthening of tau, a decrease of activity time alpha and an increase of rest time delta, resulting in a decrease of the alpha/delta ratio. These effects of Rolipram could be du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Wolfgang found that lithium slowed the circadian clocks of most plants and animals (Engelmann, 1972(Engelmann, , 2014Hofmann et al, 1978;Delius et al, 1984;Rauch et al, 1986;Schmid and Engelmann, 1987;Smietanko and Engelmann, 1989). Because some human patients had short period lengths of certain rhythmic parameters that became out of phase with the rhythm of body temperature during depression (Pflug et al, 1982), Wolfgang tested the hypothesis that lithium (and other antidepressants) has a beneficial effect on depression by prolonging the period of short-period rhythms and normalizing the phase relationship of all rhythms, a hypothesis that proved to be correct (Eckhardt et al, 1983;Pflug and Engelmann, 1987). Together with his long-time collaboration partner Anders Johnsson (biophysicist at the Norwegian University of Science and Technology, Trondheim) and Burkhard Pflug (1939Pflug ( -2009 psychiatrist at Frankfurt University Hospital), he investigated the effect of lithium on healthy human volunteers during the Arctic summer in Spitsbergen under free-running conditions.…”
mentioning
confidence: 99%
“…Wolfgang found that lithium slowed the circadian clocks of most plants and animals (Engelmann, 1972(Engelmann, , 2014Hofmann et al, 1978;Delius et al, 1984;Rauch et al, 1986;Schmid and Engelmann, 1987;Smietanko and Engelmann, 1989). Because some human patients had short period lengths of certain rhythmic parameters that became out of phase with the rhythm of body temperature during depression (Pflug et al, 1982), Wolfgang tested the hypothesis that lithium (and other antidepressants) has a beneficial effect on depression by prolonging the period of short-period rhythms and normalizing the phase relationship of all rhythms, a hypothesis that proved to be correct (Eckhardt et al, 1983;Pflug and Engelmann, 1987). Together with his long-time collaboration partner Anders Johnsson (biophysicist at the Norwegian University of Science and Technology, Trondheim) and Burkhard Pflug (1939Pflug ( -2009 psychiatrist at Frankfurt University Hospital), he investigated the effect of lithium on healthy human volunteers during the Arctic summer in Spitsbergen under free-running conditions.…”
mentioning
confidence: 99%